2020
DOI: 10.3389/fonc.2020.01507
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Plasma Metabolic and Lipidomic Characteristics of a Chinese Cohort and a Pilot Study of Renal Cell Carcinoma Biomarker

Abstract: Plasma metabolomics and lipidomics have been commonly used for biomarker discovery. Studies in white and Japanese populations suggested that gender and age can affect circulating plasma metabolite profiles; however, the metabolomics characteristics in Chinese population has not been surveyed. In our study, we applied liquid chromatography-mass spectrometry-based approach to analyze Chinese plasma metabolome and lipidome in a cohort of 534 healthy adults (aging from 15 to 79). Fatty-acid metabolism was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…Mummichog, GSEA (Gene Set Enrichment Analysis), and their combination (Mummichog +GSEA) were applied in this study, in the “MS Peaks to Pathways” module (version 1) of MetaboAnalyst 4.0 (Chong et al., 2019; Li et al., 2013; Liu et al., 2020). The input tables are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Mummichog, GSEA (Gene Set Enrichment Analysis), and their combination (Mummichog +GSEA) were applied in this study, in the “MS Peaks to Pathways” module (version 1) of MetaboAnalyst 4.0 (Chong et al., 2019; Li et al., 2013; Liu et al., 2020). The input tables are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, 13 prior case-control studies have identified potential metabolic biomarkers in plasma [6][7][8][9][10] or serum [11][12][13][14][15][16][17][18] that distinguish RCC from controls. The proposed profiles include lipids, lipoproteins [6][7][8][9][13][14][15]17,18], amino acids [6][7][8]10,[12][13][14]17], and carbohydrates [7,11,13,14,16]. However, robust RCC diagnostic biomarkers remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid and lipid metabolism are vital in RCC. Prior studies lacked systematic analyses of specific amino acids and lipids in the plasma of patients with RCC, as they mainly used qualitative mass spectrometry methods [23], such as proton nuclear magnetic resonance [7,13,16], MS or multivariate models [10][11][12]14,18], and liquid chromatography (LC)-MS [8,9,15,17]. Our study quantified plasma metabolites and lipids using an Abso-luteIDQ p400 high-resolution (HR) kit and ultra-high-performance LC (UHPLC)-MS, which allowed for absolute quantification.…”
Section: Introductionmentioning
confidence: 99%
“…Lipidomics is a more targeted model used to systemically analyze the composition and expression levels of lipid molecules [23] and has also been applied in research on diabetes [24,25] and DR [26][27][28]. Recently, an increasing number of studies have used both metabolomics and lipidomics to investigate potential biomarkers and mechanisms [29,30] and have expanded the understanding of the pathogenesis of many diseases.…”
Section: Introductionmentioning
confidence: 99%